Desenvolvimento e caracterização físico-química de molho beterraba, goiaba e tomate - Branco, Nathalia Beatriz (Universidade Federal de São Carlos, 2025)
The growing demand for convenience foods and the need for sustainable solutions for the use of fruits and vegetables have boosted the sauce market by enabling the use of perishable raw materials and adding value to the product. This study aimed to develop and characterize sauces based on guava and beetroot, exploring the potential of these ingredients, known for their high nutritional value and for contributing to sustainability by minimizing the waste of fresh food. The study consisted of developing sauces with different formulations, using varied combinations of tomato, guava and beetroot pulp. Physicochemical analyses were performed, including pH, soluble solids content, titratable acidity, water activity, color and viscosity. The guava sauce stood out for its high acidity, while the beetroot sauce presented intense color and high viscosity. In addition to the technical aspects, the study highlighted the positive impact on reducing waste and valuing local ingredients, promoting a sustainable approach to the development of new products. The use of agricultural surpluses and the transformation of perishable fruits and vegetables into sauces with a longer shelf life contribute to mitigating losses throughout the production chain, aligning with food safety and market innovation guidelines. It is concluded that the sauces developed not only meet the practicality and health expectations of modern consumers, but also represent a significant opportunity for the expansion of the sustainable food market in Brazil.
Development and physicochemical characterization of beetroot, guava and tomato sauce
Keywords: Alimentos de conveniência; Inovação; Redução de desperdícios; Frutas e hortaliças; Convenience foods; Innovation; Waste reduction; Fruits and vegetables; CIENCIAS AGRARIAS::CIENCIA E TECNOLOGIA DE ALIMENTOS::TECNOLOGIA DE ALIMENTOS; 3. Saúde e Bem-Estar; 2. Fome Zero e Agricultura Sustentável